Willingness and influential factors of parents to vaccinate their children with novel inactivated enterovirus 71 vaccines in Guangzhou, China. Issue 26 (18th June 2018) - Li, Tiegang; Wang, Hui; Lu, Yin; Li, Qin; Chen, Chun; Wang, Dahu; Li, Meixia; Li, Yilan; Lu, Jianyun; Chen, Zongqiu; Ma, Yu; Liu, Wenhui; et al.
Abstract: Hand, foot and mouth disease (HFMD) primarily affects children younger than 5 years of age. Recently, HFMD has ranked as the top notifiable infectious disease in China. In December 2015, China approved two novel inactivated enterovirus 71 vaccines (EV71 vaccines) for HFMD. Parents' acceptance is often essential for vaccination program success. The goal of this study was to identify willingness and influential factors to vaccinate among parents of kindergarteners in Guangzhou, China. A cross-sectional survey of face-to-face interviews was conducted from March to July 2016. Fifty-five kindergartens were randomly selected from 11 districts of Guangzhou. An anonymous self-designed questionnaire was used to investigate awareness, knowledge and attitude towards HFMD and EV71 vaccines. A total of 868 parents participated in the survey. Mean(±standard deviation) knowledge score of HFMD was 6.32(±1.70). Approximately 32.03% of parents had heard of the EV71 vaccines with 22.58% receiving information before this study. Nearly 44.24% of parents showed willingness to vaccinate their children. Previously receiving EV71 vaccine-related information [adjusted odds ratio (aOR) = 1.48, 95% confidence interval (CI): 1.04–2.11], no fear of adverse effects (aOR = 4.25, 95%CI: 2.77–6.53), perceived susceptibility of children to HFMD (aOR = 2.15, 95%CI: 1.42–3.25) and children not previously diagnosed with HFMD (aOR = 1.56, 95%CI: 1.07–2.27) were positively associated with EV71 vaccination acceptability. However, parental education background (aOR = 0.54, 95%CI: 0.37–0.80) was negatively correlated with vaccination acceptability. Our study provides baseline information for future vaccination campaigns to help improve the EV71 vaccine uptake rate. Special efforts are urgently needed to improve the awareness and knowledge of EV71 vaccines in China.